2021
DOI: 10.1002/lsm.23501
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficacy and safety of 308‐nm excimer laser with intralesional corticosteroids for the treatment of alopecia areata: A randomized controlled study

Abstract: Background: Corticosteroids have been the mainstay of treatment for alopecia areata (AA). Recently, the 308-nm excimer laser has been proposed for treating AA. Objectives: To compare the efficacy and safety of excimer laser with intralesional corticosteroid (ILCS) in AA. Methods: Patients with at least two alopecic patches were randomly assigned to receive weekly excimer laser treatments or monthly injections of ILCS. Photographs and trichoscopy images were examined at baseline, the last treatment session, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Several reports have demonstrated that fractional laser treatment effectively induces hair regrowth in combination with other factors, including platelet‐rich plasma, 21 hair growth factors, 39 and MSC‐conditioned medium 40 . Similar results were reported with 308 nm excimer laser/light treatment for alopecia areata (AA) 41,42 . These positive effects may be produced not only by their ability to penetrate the skin barrier, 20 but also by the inflammation and mechano‐physical signals induced by fractional laser irradiation 30,31,43 .…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Several reports have demonstrated that fractional laser treatment effectively induces hair regrowth in combination with other factors, including platelet‐rich plasma, 21 hair growth factors, 39 and MSC‐conditioned medium 40 . Similar results were reported with 308 nm excimer laser/light treatment for alopecia areata (AA) 41,42 . These positive effects may be produced not only by their ability to penetrate the skin barrier, 20 but also by the inflammation and mechano‐physical signals induced by fractional laser irradiation 30,31,43 .…”
Section: Discussionsupporting
confidence: 55%
“…40 Similar results were reported with 308 nm excimer laser/light treatment for alopecia areata (AA). 41,42 These positive effects may be produced not only by their ability to penetrate the skin barrier, 20 but also by the inflammation and mechano-physical signals induced by fractional laser irradiation. 30,31,43 Results suggest that these treatments may compensate for the signals required for hair regrowth, but are not sufficient under irradiation conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A recent retrospective study in 36 patients with AA that included patients with ophiasis AA showed that 52% achieved SALT 75 after being treated with a median of 24 sessions of 308 nm excimer laser with a median treatment duration of 12 weeks [33]. A randomized controlled study that compared 308 nm excimer lamp with intralesional corticosteroids in 99 patients, they found that at the end of the last session the mean score of hair regrowth was lower for the excimer lamp than for the intralesional corticosteroids, however, after a month, this difference was not statistically significant, finally this study showed that the group that received excimer laser sessions had less severe adverse events than the group that received intralesional corticosteroids [34]. Alopecia totalis and universalis may not benefit from this type of treatment [35].…”
Section: Discussionmentioning
confidence: 91%
“…Some of these studied protocols are given in Table 2. Of the control trials, one included 16 participants with 99 patches of AA [21]. The author of this study concluded that the excimer laser was safe and effective in AA.…”
Section: Evidence-based Studiesmentioning
confidence: 99%